Case report: A de novo RASopathy-causing SHOC2 variant in a Chinese girl with noonan syndrome-like with loose anagen hair - Wang, Qingming; Cheng, Shuangxi; Fu, Youqing; Yuan, Haiming (Frontiers in Genetics, 2022)
Background: Pathogenic variants in the RASopathy-causing SHOC2 gene have been suggested to cause Noonan syndrome-like with loose anagen hair (NS/LAH). This condition is characterized by facial features resembling Noonan syndrome (NS), short stature, growth hormone deficiency (GHD), cognitive deficits, cardiac defects, and ectodermal abnormalities, including easily pluckable, sparse, thin, slow-growing hair, hyperpigmented skin and hypernasal voice. The mutation spectrum of SHOC2 is narrow, and only 8 pathogenic variants have been identified. Methods: Here, we report a 5-year-3-month-old Chinese female who displays characteristics typical of NS and has normal neurodevelopment. Whole-exome sequencing (WES) was used to identify the causative variants. Results: Trio-based whole-exome sequencing (WES) revealed a de novo variant (c.1231A>G, p.Thr411Ala) in SHOC2. This variant has been recently reported in one subject in the literature who displayed facial features typical of NS and also presented with significant speech delays, moderate intellectual disabilities, epilepsy, bilateral sensorineural deafness and renal dysplasia. The differential phenotypes between these subjects deserve to be further investigated. Next, we reviewed the clinical pictures of NS/LAH and noticed that a recurrent SHOC2 Ser2Gly variant was more likely to result in delayed neurodevelopment and short stature, compared to other SHOC2 variants. And growth hormone (GH) therapy could improve height prognosis. It was noticed that the slight sleep problems and friendly and relatively mature personality observed in our patient may be a novel phenotype of NS/LAH. Conclusion: Our study reconfirms the pathogenic nature of the SHOC2 Thr411Ala variant. It also provides insights into the genotype-phenotype relationship in NS/LAH and a foundation for its genetic counseling, diagnosis and treatment.